VPS35 promotes cell proliferation via EGFR recycling and enhances EGFR inhibitors response in gastric cancerResearch in context - Junxian Yu; Haoran Feng; Qingqing Sang; Fangyuan Li; Mengdi Chen; Beiqin Yu; Zhuoqing Xu; Tao Pan; Xiongyan Wu; Junyi Hou; Zhenggang Zhu; Chao Yan; et al. (EBioMedicine, 2023)
Summary: Background: Vacuolar protein sorting-associated protein 35 (VPS35) is a core component of the retromer complex which mediates intracellular protein transport. It is well known that dysfunctional VPS35 functions in the accumulation of pathogenic proteins. In our previous study, VPS35 was found to be a potential gene related to poor prognosis in gastric cancer. However, the biological functions of VPS35 in gastric cancer remain unclear. Methods: Cell viability assays were performed to examine whether VPS35 affected cell proliferation. Immunoprecipitation and biotin assays showed that VPS35 bound to epidermal growth factor receptor (EGFR) in the cytoplasm and recycled it to the cell surface. Patient-derived xenografts and organoids were used to evaluate the effect of VPS35 on the response of gastric cancer to EGFR inhibitors. Findings: VPS35 expression levels were upregulated in tumour tissues and correlated with local tumour invasion and poor survival in patients with gastric cancer. VPS35 promoted cell proliferation and increased tumour growth. Mechanistically, VPS35 selectively bound to endocytosed EGFR in early endosomes and recycled it back to the cell surface, leading to the downstream activation of the ERK1/2 pathway. We also found that high VPS35 expression levels increased the sensitivity of the xenograft and organoid models to EGFR inhibitors. Interpretation: VPS35 promotes cell proliferation by recycling EGFR to the cell surface, amplifying the network of receptor trafficking. VPS35 expression levels are positively correlated with gastric cancer sensitivity to EGFR inhibitors, which offers a potential method to stratify patients for EGFR inhibitor utilisation. Funding: National Natural Science Foundation of China.